Handbook of solid waste management (McGraw-Hill, 1994)
The book offers the first truly approach to the planning, design, and management of a municipal waste management system (source reduction, toxicity reduction, recycling nad reuse, compositing, waste-to-energy combustion, and landfilling). It explores each technology and examines its problems, costs, and legal and social ramifications